2005
DOI: 10.1007/s11745-005-1467-0
|View full text |Cite
|
Sign up to set email alerts
|

Storage lipid accumulation and acyltransferase action in developing flaxseed

Abstract: Investigations of storage lipid synthesis in developing flaxseed (Linum usitatissimum) provide useful information for designing strategies to enhance the oil content and nutritional value of this crop. Lipid content and changes in the FA composition during seed development were examined in two cultivars of flax (AC Emerson and Vimy). The oil content on a dry weight basis increased steadily until about 20 d after flowering (DAF). The proportion of alpha-linolenic acid (alpha-18:3, 18:3cisDelta9,12,15) in TAG in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…As shown in Fig. 5, DGAT1-1 exhibited small but significant changes of substrate specificity toward the acyl-CoA substrates, and the highest specificity was observed with 18:3-CoA, which is in close agreement with substrate specificity data for overall microsomal DGAT activity from developing flax embryos (34).…”
Section: Flax Dgat1-1 Displayed Small But Significantly Enhancedsupporting
confidence: 86%
“…As shown in Fig. 5, DGAT1-1 exhibited small but significant changes of substrate specificity toward the acyl-CoA substrates, and the highest specificity was observed with 18:3-CoA, which is in close agreement with substrate specificity data for overall microsomal DGAT activity from developing flax embryos (34).…”
Section: Flax Dgat1-1 Displayed Small But Significantly Enhancedsupporting
confidence: 86%
“…The data from both lipid analysis and Northern blot highly suggest that the reduced linolenic acid content in soybean compared with high 18:3 accumulators is mainly due to the lower transcript level of x-3 desaturase. Byrum et al [33] found that the reduced 18:3 concentration in the soybean genotype A5 was at least partially the result of a microsomal x-3 desaturase gene with a reduced activity. Collectively, these results indicate that one can obtain B. napus, soybeans or other oilseed crops that accumulate high x-3 fatty acid levels simply by increasing expression of the x-3 desaturase gene by use of a strong promoter or trans-activation.…”
Section: Discussionmentioning
confidence: 99%
“…The acyltransferases residing in the ER are required for the esterification of FAs to the desired sn -position of the glycerol-backbone. Most likely the acyltransferases involved in the n -3 LC-PUFA synthesis are similar to those in plants (lysophospholipid acyltransferases (LPLAT), acyl-CoA:glycerol-3-phosphate acyltransferase (GPAT) and acyl-CoA:lysophosphatidic acyltransferase (LPAAT)) [117,118]. The latter two represent enzymes of the Kennedy pathway in the ER [119].…”
Section: Eicosapentaenoic Acid (Epa 20:5n-3) Synthesis In Phaedoamentioning
confidence: 99%
“…Overexpression of genes encoding high substrate specific acyltransferases would lead to a higher esterification rate of acyl-donor to a specific sn -position of the glycerol-3-phosphate or the PC. The two ER-localized enzymes of the Kennedy pathway (GPAT and LPAAT) and the LPLAT are responsible for the incorporation of activated FAs into membrane lipids, or precursors of membrane lipids [117,118]. Recently, it was shown that an ER-membrane bound TpGPAT from the marine diatom T. pseudonana affected FA composition and accumulation in triacylglycerides and phospholipids by overexpression in a GPAT-deficient yeast strain [128].…”
Section: Eicosapentaenoic Acid (Epa 20:5n-3) Synthesis In Phaedoamentioning
confidence: 99%